Meaning(s) of transition(s) from military to civilian life at the intersection with mental health: implications for clinical settings - Misca, Gabriela; Augustus, Jo; Russell, Jade; Walker, Janet (Frontiers in Psychology, 2023)
The experiences of military personnel moving into civilian life can be varied for the individual, families and communities. This paper aims to shed light on the various meanings of the multiple and “nested” transitions of military personnel to civilian life in the context of attending a mental health service in the UK. This was achieved through secondary analysis of semi-structured interviews with veterans who were engaging with a mental health service in the UK and a further interview with the mental health service lead. A thematic analysis was employed based on a descriptive phenomenological approach. Results indicate that an appropriate support infrastructure needs to be put in place for veterans prior to, during and after the transition to civilian life. The support appropriateness includes themes specific to connectedness to others, support service accessibility, mental health professionals' military culture awareness and mental health stigma. Although the findings suggest that community services need an awareness of veterans' specific needs, many of the themes are similar to those of the general population. Therefore, the need for an integrated healthcare system is essential in the transition of military service personnel to civilian life. Drawing on international evidence as well as the current findings, implications for policy and practice are highlighted throughout.